What factors determines the FDI net flows in Africa? GMM and PMG techniques - E., Abdelbagi; M., Azali; H., Azman; Md Nor, Norashidah (Omics Publishing Group, 2016)
This study investigated the determinants of FDI in Africa during the time period from 1974 to 2013, and annual data from the World Bank, African Union and United Nation. The study used GMM estimator and conducted three estimations, namely, 5 years, 8 years and 10 years average’ estimations. Besides, to robustness check the results, the study used PMG estimator and therefore the full sample countries has been divided into three groups according to the income level, namely, low-income, lower middle-income and upper middle-income groups. The results suggested that the net inflows of the FDI in Africa are determined by economic growth, human capital, infrastructure, domestic investment and trade openness of the region.